Perspectives on clinical leadership: a qualitative study exploring the views of senior healthcare leaders in the UK - Nicol, Edward D (SAGE Publications, 2014)
INTRODUCTION: Clinicians are being asked to play a major role leading the NHS. While much is written on about clinical leadership, little research in the medical literature has examined perceptions of the term or mapped the perceived attributes required for success. OBJECTIVE: To capture the views of senior UK healthcare leaders regarding their perception of the term `clinical leadership' and the cultural backdrop in which it is being espoused. SETTING: UK Healthcare sector PARTICIPANTS: Senior UK Healthcare leaders METHODS: Twenty senior healthcare leaders including a former Health Minister, NHS Executives, NHS Strategic Health Authority, PCT and Acute Trust chief executives and medical directors, Medical Deans and other key actors in the UK medical leadership arena were interviewed between 2010 and 2011 using a semi-structured interview technique. Using grounded theory, themes were identified and subsequently analysed in an attempt to answer the broad questions posed. MAIN OUTCOME MEASURES: Not applicable for a qualitative research project RESULTS: A number of themes emerged from this qualitative study. First, there was evidence of changing attitudes among doctors, particularly trainees, towards becoming involved in clinical leadership. However, there was unease over the ambiguity of the term ‘clinical leadership’ and the implications for the future. There was, however, broad agreement as to the perceived attributes and skills required for success in healthcare leadership. CONCLUSIONS: Clinical leadership is often perceived to be doctor centric and ‘Healthcare Leadership’ may be a more inclusive term. An understanding of the historical medico-political context of the leadership debate is required by all healthcare leaders to fully understand the challenges of changing healthcare culture. Whilst the broad attributes deemed essential for success as a healthcare leaders are not new, significant effort and investment, including a physical Healthcare Academy, are required to best utilise and harmonise the breadth of leadership talent in the NHS.